The Effect of Good Corporate Governance and Liquidity Mechanisms on Financial Performance (Empirical Study on Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2022 Period) - TAKAIN, Yimna Aprida; HIDAYAH, Nurul (PT Keberlanjutan Strategis Indonesia, 2024)
This study examines the effect of Good Corporate Governance and liquidity mechanisms on financial performance in property and real estate sub-sector companies listed on the Indonesia Stock Exchange. Good corporate governance in this study is proxied with independent commissioners, audit committees, and institutional ownership. Liquidity is proxied by the current ratio. Financial performance is proxied by returns on assets (ROA). The purpose of this study is to analyze the influence of independent commissioners, audit committees, institutional ownership and current ratios on financial performance. The formulation of the problem in this study is whether independent commissioners, audit committees, institutional ownership and current ratios affect financial performance. The methods used in this study are descriptive methods and explanatory causal methods with a quantitative approach. The results of this study show that independent commissioners and institutional ownership have no effect on financial performance. While the audit committee and current ratio have a negative and significant effect on financial performance.